Evidence on trends in wellbeing of rural Ethiopian households during the COVID-19 pandemic - Alderman, Harold; Gilligan, Daniel O.; Hidrobo, Melissa; Leight, Jessica; Taffesse, Alemayehu Seyoum; Tambet, Heleene (International Food Policy Research Institute, 2021)
The COVID-19 pandemic continues to be a significant threat to public health throughout most of the world as the coronavirus continues to spread, mostly unchecked by limited availability of vaccines, and largescale surges in cases are fed by new variants of the virus. In Ethiopia, surges in COVID-19 cases after months of apparently low levels of infection have periodically required renewed restrictions locally to control the spread of the virus. Thus, it is necessary to review available date to understand the effects of the COVID-19 pandemic on households in Ethiopia, and particularly on the poorest households, who are more vulnerable to protracted effects of the virus and associated restrictions on activity as a result of their limited resources. We present results of two rounds of a phone survey, conducted in June and August 2020, respectively, of around 1,200 rural households. All households in the sample are beneficiaries of the fourth phase of Ethiopia’s Productive Safety Net Program (PSNP4) and also participate in the USAID-funded Strengthening PSNP4 Institutions and Resilience (SPIR) project, implemented by World Vision, CARE and ORDA in North Wollo and Wag Himra zones in Amhara, and primarily in East and West Hararghe zones in Oromia. The targeted phone survey respondents were adult males from sample households in IFPRI’s experimental impact evaluation of SPIR who provided a phone number during the 2019 midline survey. This is a subsample of the broader SPIR evaluation sample as 33% of households provided a phone number and thus were eligible for inclusion in the phone survey. Available evidence suggests that households who provided a phone number are characterized by higher socioeconomic status vis-à-vis other SPIR households in the study sample who did not provide a phone number. However, as all households in the phone survey are SPIR beneficiaries, they are still relatively poor in the broader context of rural Ethiopia. We report evidence from the two survey rounds on coronavirus awareness and protective measures taken; changes in livelihoods, including crop production and livestock raising; access to and utilization of markets; changes in food consumption and food security; experience with desert locusts and fall armyworms; and exposure to public programming.